Strategies Employed by Principals to Overcome Stress in Performance of their work in Secondary Schools in Kisumu County - Ogalo, Sophia Atieno; Odera, Florence; Ogogo, Collins (International Journal of Education and Research, 2020)
Globally, there has been an outcry on stress by the principals in the management of public secondary schools in Kisumu County, Kenya. Stress comes about when the principal is subjected to unusual situations such as students’ strike, destruction of school properties, teachers transfer or when there are uncalled for demand on the principal and teachers absenteeism. Principals who are stressed cannot provide effective leadership and management. Therefore, there is need to examine problems of principals’ stress, strategic management and planning to implement. The objective of this study was to identify strategies employed by the principals to overcome stress in their work performance in schools. The study adopted the Cognitive Activation Theory of Stress (CATS) developed by Levine Ursin (1991). The target population was two hundred and twenty principals, two hundred and twenty deputy principals and seven Sub-County Quality Assurance and Standards Officers (SCQASOs) in the county. Stratified random sampling was used to select schools, while purposive, stratified and simple random sampling methods were used to select both principals and the deputy principals in various categories of schools. Saturated sampling technique was used to select Sub-County Quality Assurance and Standards Officers. Instruments for data collection included questionnaire, document analysis and interview schedule. Questionnaire was used to collect information from both principals and the deputy principals and interview schedule was used to collect data from the Sub-County Quality Assurance and Standards Officers. Document analysis was employed to gather information about the principals’ transfers, category of schools and performance of the students in the national examinations from the Teachers Service Commission and the Ministry of Education department respectively. The research design was descriptive survey that used qualitative analysis and quantitative statistics in analyzing the data. The results were presented qualitatively into emerging themes and then reported in verbatim form, while quantitative data were analyzed using descriptive statistics such as frequency counts, mean, percentage and standard deviation using Statistical Package for the Social Sciences Programme (SPSS). The study found out that the strategies that were used by the principals to overcome stress included: positive attitude towards self and others, effective management of time, delegation of duties to the staff, seeking support from other school stakeholders, sharing a meal with the family, socializing with the staff members, control of anger, leisure activities, spending time with students at free time, seeking medical help, seeking counseling, keeping praise files, and physical exercise respectively. The study recommended that the government of Kenya through (TSC) should employ more trained counselors and locate them at strategic places like schools, within each sub-county to help principals in solving stress issues and teachers to be trained on leadership in order to handle administrative duties amicably.
Keywords: Stress; strategies; principals; secondary schools; overcome; Kisumu County